A multi-millennial record of rock glacier ice chemistry (Lazaun, Italy) - Nickus, Ulrike; Thies, Hansjörg; Krainer, Karl; Lang, Kathrin; Mair, Volkmar; Tonidandel, David (Frontiers in Earth Science, 2023)
Active rock glaciers – known as mixtures of unconsolidated debris and interstitial ice - are widespread indicators of alpine permafrost. The age of a frozen rock glacier core in the Central European Alps (Lazaun, Italy) was dated to about 10000 years. Here we report on the chemical composition of the frozen Lazaun core. The ice containing part of the core extended from about 2.8 m down to 24 m depth and consisted of two lobes - both a mix of ice and debris, separated by a 2 m thick ice-free layer. The two lobes of the core showed layers of high solute content and peak values of electrical conductivity exceeding 1000 µS/cm, but they differed in acidity and metal concentration. High acidity (minimum pH of 4.15) and high levels of elements like nickel, cobalt, zinc, manganese, iron and aluminum characterized the upper lobe, while neutral to alkaline pH and low metal values prevailed in the bottom lobe. We attributed solutes accumulated in the ice matrix to the weathering of bedrock minerals, with peak values favored by the oxidation of pyrite, or by an enhanced reactive surface area in fine-grained sediment layers. The chemical composition of the ice core also revealed signals of prehistoric atmospheric deposition from different sources including wood combustion, metal ore mining, and large volcanic eruptions (Thera, Aniakchak II). To our knowledge, this is the first study that presents the chemical stratigraphy of an entire rock glacier ice core.